Ingestion of bacterially expressed double-stranded RNA inhibits gene expression in planarians - Newmark, Phillip A. (National Academy of Sciences, 2003)
Freshwater planarian flatworms are capable of regenerating complete organisms from tiny fragments of their bodies; the basis for this regenerative prowess is an experimentally accessible stem cell population that is present in the adult planarian. The study of these organisms, classic experimental models for investigating metazoan regeneration, has been revitalized by the application of modern molecular biological approaches. The identification of thousands of unique planarian ESTs, coupled with large-scale whole-mount in situ hybridization screens, and the ability to inhibit planarian gene expression through double-stranded RNA-mediated genetic interference, provide a wealth of tools for studying the molecular mechanisms that regulate tissue regeneration and stem cell biology in these organisms. Here we show that, as in Caenorhabditis elegans, ingestion of bacterially expressed double-stranded RNA can inhibit gene expression in planarians. This inhibition persists throughout the process of regeneration, allowing phenotypes with disrupted regenerative patterning to be identified. These results pave the way for large-scale screens for genes involved in regenerative processes.